To translate the line \( y = -x + 1 \) one unit to the right and two units up, we can follow these steps:
-
Translation 1 unit to the right: This affects the \( x \)-coordinate, so we replace \( x \) with \( x - 1 \) in the equation:
\[ y = - (x - 1) + 1 \]
Simplifying this, we get:
\[ y = -x + 1 + 1 = -x + 2 \]
-
Translation 2 units up: This affects the \( y \)-coordinate, so we add 2 to the \( y \) value:
\[ y = -x + 2 + 2 = -x + 4 \]
The final equation of the translated line is:
\[ y = -x + 4 \]
Thus, the answer is:
y = -x + 4.